The Influence of Entrepreneurial Activity’s Innovation on Job Creation - Al-Alawi, Abrar Mohammed; Alkindi , Kawther Salim; Al-Shukaili, Abdullah; Ahmed, Essia Ries (International Journal of Industrial Management, 2022)
The purpose of this study is to explore the influence of innovation in the total early entrepreneurial business activities (TEA) (i.e. nascent and new entrepreneurs) on job creation in the Sultanate of Oman. In other words, the objective of this research is to examine the extent to which current innovation types in entrepreneurial activities have an impact on creating jobs. The TEA innovation will be measured by the ability of the enterprise to adopt new technology and the ability to create new products or services in the market. Based on the existing empirical studies, a conceptual model has been developed accordingly. To achieve the research objective, this study applied the data collected from national Omanis at the individual level using the Global Entrepreneurship Monitor (GEM) data 2020 to test the stated hypotheses. The sample of this study consist of 2000 Omani households who are involved in business entrepreneurial activities. Using structural equation modeling in PLS (SEM-PLS). The results revealed that the innovation in nascent and new entrepreneurs affects the level of created jobs in the Sultanate of Oman. The findings also demonstrate nascent and new entrepreneurs’ innovativeness ability to create jobs reflected significantly on both current and expected creation of jobs.